Strategi komunikasi dinas komunikasi dan informatika kota Salatiga dalam mensosialisasikan program “Matur Mas Yuli” - Alodia Linsi Fandita; Rini Darmastuti (Universitas Garut, 2023)
Abstract The Matur Mas Yuli Program is one of the online aspirations and complaint service portals owned by the Salatiga City Government. This program is a communication bridge between the people of Salatiga City and the Mayor of Salatiga. Many Salatiga residents do not know about this program, due to lack of outreach from the government. There are several problems that occur if the public does not report complaints through Matur Mas Yuli. One of the consequences is that many people's voices are not heard by the Salatiga government, therefore the government uses information technology to reduce this problem. The aim of this research is to explain the communication strategy in socializing the